2016
DOI: 10.1002/jmri.25214
|View full text |Cite
|
Sign up to set email alerts
|

Design of a breast phantom for quantitative MRI

Abstract: Purpose We present a breast phantom designed to enable quantitative assessment of measurements of T1 relaxation time, apparent diffusion coefficient (ADC), and other attributes of breast tissue, with long-term support from a national metrology institute. Materials and Methods A breast phantom was created with two independent, interchangeable units for diffusion and T1/T2 relaxation, each with flexible outer shells. The T1 unit was filled with corn syrup solution and grapeseed oil to mimic the relaxation beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 18 publications
(30 reference statements)
2
67
2
Order By: Relevance
“…The breast phantom evaluated in this study was created as two distinct interchangeable units: one for diffusion and distortion evaluation and one for T 1 relaxation evaluation (9) (Figure 1). The interchangeable nature allows each phantom unit to be imaged on each side of the coil, thereby allowing examination of differences between the left and right sides of the coil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast phantom evaluated in this study was created as two distinct interchangeable units: one for diffusion and distortion evaluation and one for T 1 relaxation evaluation (9) (Figure 1). The interchangeable nature allows each phantom unit to be imaged on each side of the coil, thereby allowing examination of differences between the left and right sides of the coil.…”
Section: Methodsmentioning
confidence: 99%
“…Rather than providing absolute estimates and CIs of standard deviations to estimate repeatability , we provide the standard deviations in comparison to a particular baseline scanner-coil-sequence combination. The baseline scanner-coil-sequence combination for ADC was chosen to be that with measured ADC values closest to the reference measurements acquired using a spin-echo sequence with diffusion-weighted gradients (9), Configuration “1.5Ta – 2 b-value” (Tables 1 and 2). A relative standard deviation less than one is more repeatable than the baseline, and above one is less repeatable than the baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The outer container is dependent on both the anatomy of interest and the RF hardware in use (eg, a 15.0 cm diameter sphere is not a good match for a breast coil). Previous work demonstrated that using phantoms with correct geometry for the anatomy of interest, which is also appropriately sized for the RF hardware, is important for assessing quantitative imaging performance . The reference solutions within the phantom are dictated by the quantitative parameters of interest.…”
Section: Deployed Nist Reference Objectsmentioning
confidence: 99%
“…Finally, the UCSF/NIST breast phantom, which has T 1 and ADC values representative of fibroglandular and fat tissue, was used by the I‐SPY 2 clinical trial . The phantom is designed to test both sides of breast coils, which requires a unique geometry.…”
Section: Deployed Nist Reference Objectsmentioning
confidence: 99%
See 1 more Smart Citation